Governance Dynamics in Indonesia's Salt Industry: Evidence from Jeneponto - Sally, Manrancai; Sangkala, ‎; Nara, Nurdin; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
This study examines the dynamics of governance in the Indonesian salt industry with a particular focus on Jeneponto Regency, one of the central salt-producing regions in Indonesia. Using a systematic qualitative literature review approach supported by NVivo-based thematic mapping, it aims to identify dominant patterns, institutional challenges, and epistemic gaps in academic discourse on salt sector governance. Two analytical tools, namely comparison by coding references and items clustered by word similarity, are used to explore the density of themes and semantic linkages among selected literature. The analysis results show that the literature focuses on technical production issues, farmer income inequality, and national policy interventions. However, the results of semantic clustering reveal deeper mismatches between the national regulatory framework and local implementation, especially regarding access to capital, distribution mechanisms, and institutional performance. This study also highlights the limited academic attention to participatory governance models, regional innovation, and bottom-up institutional strengthening, indicating a top-down policy bias in the literature and practice. The Jeneponto case shows that governance is still fragmented and asymmetric, constrained by weak institutional capacity, limited coordination between stakeholders, and weak consistency in policy implementation. This study recommends applying a systems thinking approach that integrates technical, institutional, and policy dimensions into a coherent and inclusive governance model to address these challenges. This article contributes conceptually and practically to the development of coastal resource governance and provides strategic insights for evidence-based policy reform in the Indonesian salt sector.